2018
DOI: 10.20471/acc.2018.57.04.05
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Blood Pressure Components on Left Ventricular Hypertrophy Remodeling

Abstract: SUMMARY – According to present findings, the impact of particular arterial pressure components on the occurrence of left ventricular hypertrophy (LVH) differs. We sought to determine which individual component of arterial pressure has the greatest impact on the LVH geometric pattern/degree. The study included 192 patients (87 men), aged 43-80 (median 68) years with hypertension and LVH. Patients were classified into three groups according to type of hypertrophy (concentric, eccentric and asymmetric) and into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Higher ACPA was also associated with the presence of citrullinated protein within atherosclerotic plaques, which may play a role in the large atherosclerotic burden, leading to the impaired resolution of inflammation within the atherosclerotic plaque [52] . Increased SBP and NSAID use were related to increased LVMI could be explained by the SBP was modified left ventricular mass [53] with confirm by the high prevalence of left ventricular hypertrophy [54] and NSAIDs enhanced the effect of angiotension II [55] with causing abnormal finding on echocardiography [56] .…”
Section: Discussionmentioning
confidence: 95%
“…Higher ACPA was also associated with the presence of citrullinated protein within atherosclerotic plaques, which may play a role in the large atherosclerotic burden, leading to the impaired resolution of inflammation within the atherosclerotic plaque [52] . Increased SBP and NSAID use were related to increased LVMI could be explained by the SBP was modified left ventricular mass [53] with confirm by the high prevalence of left ventricular hypertrophy [54] and NSAIDs enhanced the effect of angiotension II [55] with causing abnormal finding on echocardiography [56] .…”
Section: Discussionmentioning
confidence: 95%
“…The study demonstrated that the risk of all-cause and other causes of mortality increased with increasing PP [ 15 ]. Pulse pressure was also described to predict left ventricular remodelling and left ventricular hypertrophy, particularly of the concentric type that is a significant independent risk factor for increased cardiovascular morbidity and mortality [ 16 , 17 ]. The use of ABPM is beneficial; however, it entails the availability of special equipment, knowledgeable personnel and time for interpretation, and thus, its accessibility may be limited in the outpatient care settings.…”
Section: Introductionmentioning
confidence: 99%
“…The aldosterone synthase gene (CYP11B2), which is the main regulator of aldosterone activity in plasma, according to previous studies, had a significant effect on blood pressure and the severity of structural and functional changes in the myocardium in patients with hypertension [6,7,16,19]. Myocardial fibrosis is also an important sign of hypertensive heart, which is currently more difficult to detect than the actual LV hypertrophy [9,22].…”
Section: Introductionmentioning
confidence: 99%